An empirical study on traditional culture and interdisciplinary teaching: a case study of the San Zhao Lantern - Chen, Shanwei; Huang, Boyi; Jin, Guo; Duan, Xixi (Frontiers in Education, 2025)
IntroductionIntegrating Chinese traditional culture into modern education is increasingly emphasized, yet effective methods remain underexplored. This study investigates how traditional cultural elements, specifically the San Zhao Lantern, can enhance interdisciplinary teaching, using the Stimulus-Organism-Response (S-O-R) framework.MethodsThe study involved 5th and 6th-grade students from G Primary School in City B. Data were collected through classroom observations, questionnaires, and learning outcome assessments to evaluate students’ cultural identity, learning interest, and classroom engagement in an interdisciplinary teaching context incorporating the San Zhao Lantern.ResultsThe integration of traditional cultural elements significantly enhanced students’ cultural identity, increased learning interest, and improved classroom engagement.DiscussionThese findings provide empirical support for incorporating traditional culture into modern education, validating the effectiveness of interdisciplinary teaching designs under the S-O-R framework. This study offers new perspectives for educational practice, highlighting the potential of cultural elements like the San Zhao Lantern to enrich teaching.